ASSESSING THE CORPORATE ENTREPENEURSHIP WITHIN MEDIUM ENTERPRISE, CASE STUDY: DOUBLE DEER MUSIC FINAL PROJECT - Anggraini, Dian; Dellyana, Dina (Journal of Business and Management, 2018)
Abstract.Â A concept of corporate entrepreneurship corresponds to the increase in growth of small and medium enterprises (SMEs). This concept promotes the ability of employees in creating values within the organization and encourages them to pursue innovative activities. However, managers are still unaware of the role of corporate entrepreneurship and the importance of measuring it. The measurement of corporate entrepreneurship enables management objectively to assess the culture and readiness of the organization to participate in corporate entrepreneurial activities. The author selected Double Deer Music as the research object, a medium enterprise that offers innovation and technology as its main value proposition. Throughout its business model development, the internal organization is stated as the main problem. To overcome the issue, the research methodology used is multi-method, qualitative research and quantitative research using Corporate Entrepreneurship Assessment Instrument (CEAI) by Kuratko, Hornsby and Covin (2014). The result will reveal the current level of corporate entrepreneurship within Double Deer Music. Divisional perception of corporate entrepreneurship within Double Deer Music is also examined. A session is held with each division to report the score and identify the perceived gaps on the current organizational boundaries in Double Deer Music.Â Keywords: Business Model, Corporate Entrepreneurship, Corporate Entrepreneurship Assessment Instrument, Small and Medium Enterprise.